The Urgency of Total Economic Value Aspect in Food Security Regulation In Order to Engage Asia's Trade Area(Indonesia Case Study) - Anugrah Adiastuti (UBL, 2013)
international trade community has comparative advantageous such as diverse food products that can beused as means in addressing market competition. These, Indonesia, advantageous, currently, have notaccelerated Indonesia’s food security position either from state income or agricultural supportingproducts. Moreover, total economic value has also not been implied into national regulations. Thoseprevious problems shall be completed into a better improvement by including the considerations of totaleconomic value to many regulations controlling food security. This review is undertaken by having tradetheory, food security regulation, and field data analysis. By covering total economic value aspect,hopefully, it helps better position for Indonesia in optimizing food security and increasing state (tradequantity and quality) incomes and quality of life of the society itself.